Le Monument De Pasteur Place De Breteuil - Andrieux, Clément Auguste; Carrey, active 1900 (Louis Andrieux, 1904)
Front cover illustration for the French newspaper, Le Petit Parisien (published between 1876 and 1944). The illustration features the statue of Louis Pasteur that stands in the center of Le Place de Breteuil in Paris. The statue of Pasteur was built in 1904 by sculptor Alexandre Falguière.
Keywords: Periodicals; Pasteur, Louis, 1822-1895; Monuments